Six creative writing activities based on everyday objects (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
All of us –students and teachers– are tired of repeating again and again the same writing activities. Introducing creativity in our classrooms is easier than it looks. This essay proposes six creative writing activities based on common objects that we use daily. We need only look around, choose an object, and start.
Keywords: creative writing; didactics; spanish as a foreign language